PERFORMANCE EVALUATION OF BLACK SOAP (TOILET SOAP) BLENDED WITH DE-OILED JATROPHA CAKE ADDITIVE AS SOLID LUBRICANT IN DIRECT COLD EXTRUSION OF ALUMINIUM ALLOYS - Yisa Tufion Albert, Waindim; David T. , Gundu; A. , Ashwe; Kuhe, Aondoyila (International Journal of Engineering Science Technologies, 2022)
The use of petro-lubricants in metal forming leads to lamination of oxide on the extrudates due to temperature increase and reaction of the base metal with some elements in the lubricant, hence resulting poor surface quality of the end product. The non-biodegradability of these lubricants also leads to environmental pollution. Although De-oiled Jatropha Caked has been volarised for so many applications, with some oil left in the cake it can still be employed for use in other applications. In this paper a bio-solid lubricant is formulated from Black soap (Toilet soap-vegetable oil-based) as base and De-oiled Jatropha cake as additive. Jatropha seeds were processed to ≤ 0.5 um particles size powder and de-oiled using Soxhlet apparatus. Black soap and de-oiled Jatropha cake was then mixed in ratios: 90:10, 80:20, 70:30, 60:40 and 50:50. Each of these was further mixed with de-ionized lukewarm water in ratio 50:50 by weight to produce solid lubricant blends B1, B2, B3, B4 and B5, respectively. Each of the Black soap-enriched solid lubricant blends were then used to test for coefficient of friction on mirrored surface prepared aluminum specimens using Ball-on-disc Tribometer. The solid lubricant blends were again used to conduct Extrusion tests on Ø25.4 mm by 25.4mm aluminum alloy billets in direct cold extrusion process on a 2000 KN capacity UT CO821 machine. The results showed blend B3 (70:30) recording the minimum coefficient of friction and extrusion force values μ=0.732 and 170.53KN, respectively. These results reveal that enriched solid lubricant B3 (70:30) is most suitable for aluminum alloys extrusion.